Early predictors of rapidly evolving multiple sclerosis: A case report - Fernando, Kryshani T.M.; James, Michael (Journal of neuroimmunology, 2017)
Objective The aim of this case report is to highlight some important features of rapidly evolving Multiple Sclerosis. In a small proportion of patients, Multiple Sclerosis (MS) can present as a fulminant disease characterised by severe and frequent relapses. This form of rapidly evolving MS is associated with significant morbidity and mortality. It is therefore important to identify these patients as early as possible, so that they can be managed effectively. However, due to the rarity of fulminant forms of MS, there is limited data on the natural history and management of this condition. We present a young man with rapidly evolving Multiple Sclerosis (MS) who had 2 disabling relapses within 14weeks. He had an unusually high CSF white cell count at presentation (86per mm3; 100% lymphocytes, 97% T cells, 3% B cells), with positive oligoclonal bands. Brain MRI showed large, cavitating lesions, with no enhancement. He required a prolonged course of intravenous methyl-prednisolone and plasma exchange. This case suggests that male gender, young age at onset, time to second relapse, relapse severity, high CSF white cell count at presentation, large and cavitating lesions on MRI may be early predictors of rapidly evolving MS. It also highlights the therapeutic value of plasma exchange and longer courses of intravenous methylprednisolone in managing severe MS relapses. Enhancement may not always be a reliable indicator of disease activity, particularly in clinical settings where single dose gadolinium is used, due to its low sensitivity in detecting blood brain barrier leakage.